Translations of racist discourse from English to Malay language in the subtitles of the Rush Hour movie franchise - Mohd Zubir, Nur Athirah; Turiman, Syamimi (Universiti Teknologi MARA, 2024)
Movies frequently feature depictions of reality in various aspects, such as the projection of racist discourse in every-day dialogue. However, translating racist discourse, particularly in the movie subtitles requires careful consideration of the target audience, source text, and cultural context to present appropriate subtitles. Despite few studies on Eng-lish-to-Malay translations of subtitles, there is a gap in the exploration of translation strategies of racist discourse in English movies. Hence, this study aims to identify the racist discourse in the Rush Hour movie franchise and investi-gate the strategies used in translating racist discourse in the Malay subtitles. This qualitative study utilised Martin and White’s (2005) Appraisal Theory to identify and categorise the racist discourse and Gottlieb’s (1992) subtitling strate-gies to analyse the strategies used in translating racist discourse. The results reveal that all three types of racist dis-course were evident in the movies, namely 1) affect, to show negative emotions and responses towards others, driven by racial, ethnic or religious differences (e.g., I will slap you so hard, you’ll end up in the Ming dynasty); 2) apprecia-tion, referring to rigidly using certain traits as ample reasons for unfavourable judgements (e.g. First I get a bullshit assignment, now Mr. Rice-A-Roni… don’t even speak American) and 3) judgement, which describes negative judge-ments of people’s behaviour when seen as aligned with their racial or ethnic differences (e.g., Hey! Slow down Chen/Chin! Hell is wrong with you?). The top five subtitling strategies in the Malay subtitles of racist discourse in the movies, i.e. paraphrase, transfer, imitation, decimation, and resignation were also presented and elaborated. The find-ings of this study may benefit translators, subtitlers, and screenwriters for them to consider the sociocultural norms and context in the translation process.